Using Electronic Mail for Data Collection in Organizational Research - Sproull, Lee (Academy of Management Journal, 1986)
In this article the author discusses a study he conducted that examined the effectiveness of using electronic mail for carrying out research. He notes that some of the benefits of using electronic mail in research are that it is a less costly method than having to hold interviews, messages are sent at the convenience of the sender and read at the convenience of the respondent, respondents have the option of creating a hard copy of the message or can chose to delete the message and users can process their own mail, cutting down the work of secretaries. The author notes that some of the obstacles in using electronic mail are the respondents access to a computer, their willingness to respond to such surveys and the value of such data as compared to that collected by conventional means.